2020
DOI: 10.3389/fsurg.2020.554910
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Impact of Pathology on Patients With Pseudomyxoma Peritonei Undergoing Debulking Surgery: A Systematic Review and Meta-Analysis of Retrospective Studies

Abstract: Background: Pseudomyxoma peritonei (PMP) is a rare clinical condition with fatal outcomes, which is characterized by the progressive accumulation of mucinous ascites and peritoneal implants. Some studies have reported the effect of PMP biology on patient outcome. The objective of this study was to analyze published articles focusing on the impact of pathology on the prognosis of PMP patients undergoing debulking. Methods: Data from all studies regarding the prognosis of patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 46 publications
(48 reference statements)
2
7
0
Order By: Relevance
“…The results are easily affected by the experience level of pathologists, the complexity of images and the visual search process, which leads to inaccurate pathological diagnosis. It showed that pathological type is an independent prognostic factor in PMP patients [10]. However, Mhhamed et al [11] found that although most DPAM patients had a relatively better prognosis, some DPAM patients showed highly aggressive disease progression, with a 5-year survival rate much lower than those patients with worse tumor differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results are easily affected by the experience level of pathologists, the complexity of images and the visual search process, which leads to inaccurate pathological diagnosis. It showed that pathological type is an independent prognostic factor in PMP patients [10]. However, Mhhamed et al [11] found that although most DPAM patients had a relatively better prognosis, some DPAM patients showed highly aggressive disease progression, with a 5-year survival rate much lower than those patients with worse tumor differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown that histopathological type is an independent prognostic factor in PMP patients. Zhou et al [10] searched studies of PMP patients underwent debulking surgery from PubMed, Wiley Online Library and Cochrane Library before Jan. 2020. 766 patients were included for Meta-analysis of pathological indicators and survival, and it showed that the 5-year survival rate of PMP patients with different pathological types after surgery was signi cantly different, and the low-grade biological behavior of PMP had a better survival comparing with high-grade PMP.…”
Section: Vangangelt Et Almentioning
confidence: 99%
“…The results are easily affected by the experience level of pathologists, the complexity of images and the visual search process, which leads to inaccurate pathological diagnosis. This showed that pathological type is an independent prognostic factor in PMP patients [ 12 ]. However, Mhhamed et al [ 13 ] found that although most LG-PMP patients had a relatively better prognosis, some LG-PMP patients showed highly aggressive disease progression, with a 5-year survival rate much lower than those of patients with worse tumor differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown that histopathological type is an independent prognostic factor in PMP patients. Zhou et al [ 12 ] conducted a meta-analysis of 766 PMP patients who underwent debulking and showed that LG-PMP had better survival than HG-PMP. Yan et al [ 22 ] performed a clinicopathological and immunohistochemical analysis of 155 PMP patients undergoing CRS+HIPEC.…”
Section: Discussionmentioning
confidence: 99%
“… 41 Other voices argued that palliative resection has proved its superiority in safety and effectiveness under that circumstance. 42 Tumor in bulk brings about volume effect related adverse impact and patient’s condition deteriorates in fast pace, if not intervene. Postoperative complications, the complexity of surgical procedure and the perplexed scope of the operation all add difficulties to make the treatment decision.…”
Section: Standard Regimen Of Pmp Treatmentmentioning
confidence: 99%